PAHs in decaying Quercus ilex leaf litter: Mutual effects on litter decomposition and PAH dynamics - De Nicola, F; Baldantoni, D; Alfani, a (Chemosphere, 2014)
The investigation of the relationships between litter decomposition and polycyclic aromatic hydrocarbons (PAHs) is important to shed light not only on the effects of these pollutants on fundamental ecosystem processes, such as litter decomposition, but also on the degradation of these pollutants by soil microbial community. This allows to understand the effect of atmospheric PAH contamination on soil PAH content via litterfall. At this aim, we studied mass and PAH dynamics of Quercus ilex leaf litters collected from urban, industrial and remote sites, incubated in mesocosms under controlled conditions for 361d. The results highlighted a litter decomposition rate of leaves sampled in urban>industrial>remote sites; the faster decomposition of litter of the urban site is also related to the low C/N ratio of the leaves. The PAHs showed concentrations at the beginning of the incubation of 887, 650 and 143ngg−1d.w., respectively in leaf litters from urban, industrial and remote sites. The PAHs in litter decreased along the time, with the same trend observed for mass litter, showing the highest decrease at 361d for the urban leaf litter. Anyway, PAH dynamics in all the litters exhibited two phases of loss, separated by a PAH increase observed at 246d and mainly linked to benzo[e]pyrene.
Keywords: C/N ratio; decomposition; Holm oak; Litter bags; Litter PAH contamination

Fungal diversity of saprotrophic litter fungi in a Mediterranean maquis environment - Lunghini, D; Granito, V M; Di Lonardo, D P; Maggi, O; Persiani, A M (MYCOLOGIA, 2013)
Monospecific and mixed-leaf litters from plant species of Mediterranean maquis (Quercus ilex, Phillyrea angustifolia, Pistacia lentiscus, Cistus spp.) in an undisturbed area in southern Italy were studied with respect to the structure and composition of their decomposer fungal community over an incubation period of 403 d. The data matrix structure was analyzed by means of detrended correspondence analysis (DCA), while indicator species analysis (ISA) was used to determine the preferential association of species with a substrate, a succession phase and monospecific/mixed experimental conditions. The ecological nature of the gradient expressed by the DCA axes was investigated by means of experimental and main chemical leaf-litter variables. The litter mixture had non-additive effects on the decomposition process even though the fungal species richness of the mixed litter was considerably higher than that of the monospecific litter. Our findings highlight the occurrence of shifts in the fungal community during decomposition in response to changes in the substrate, such as those related to the cellulose content and lignin/N ratio.
Keywords: decomposition; fungal biodiversity; leaf-litter quality; Litter bags; Mediterranean maquis; monospecific/mixed litter

Litter quality assessed by solid state 13C NMR spectroscopy predicts decay rate better than C/N and Lignin/N ratios - Bonanomi, Giuliano; Incerti, Guido; Giannino, Francesco; Mingo, Antonio; Lanzotti, Virginia; Mazzoleni, Stefano (Soil Biology and Biochemistry, 2013)
Predictions of litter decomposition rates are critical for modelling biogeochemical cycling in terrestrial ecosystems and forecasting organic carbon and nutrient stock balances. Litter quality, besides climatic conditions, is recognized as a main factor affecting decay rates and it has been traditionally assessed by the C/N and lignin/N ratios of undecomposed materials. Here, solid state 13 C NMR spectroscopy and proximate chemical analysis have been used to characterize litter organic C in a litterbag experiment with 64 different litter types decomposing under controlled conditions of temperature and water content. A statistical comparative analysis provided evidence that C/N and lignin/N ratios, showing different trends of correlation with decay rates at different decomposition stages, can be used to describe the quality of undecomposed litter, but are unable to predict mass loss of already decomposed materials. A principal component regression (PCR) model based on 13 C NMR spectra, ﬁtted and cross-validated by using either two randomly selected sets of litter types, showed highly ﬁtting predictions of observed decay rates throughout the decomposition process. The simple ratio 70e75/52e57 corresponding to Oalkyl C of carbohydrates and methoxyl C of lignin, respectively, showed the highest correlation with decay rate among different tested parameters. These ﬁndings enhance our understanding of litter quality, and improve our ability to predict decomposition dynamics. The 13 C NMR-based 70e75/52e57 ratio is proposed as an alternative to C/N and lignin/N ratios for application in experimental and modelling work
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: C stocks; C-cycle; decomposition; litter quality; litterbag; Principal component regression; Proximate cellulose and lignin

Ozone fumigation of Quercus ilex L. slows down leaf litter decomposition with no detectable change in leaf composition - Baldantoni, Daniela; Bellino, Alessandro; Manes, Fausto; Alfani, Anna (ANNALS OF FOREST SCIENCE, 2013)
The evaluation of changes in litter decomposition rate due to increasing trend in tropospheric ozone is an emerging field of investigation, providing relevant information on long-term forest ecosystem sustainability. This research aims to clarify the effects of ozone exposure on Quercus ilex leaf chemical composition and decomposition slow down. Young plants were fumigated in growth chambers at a cumulative dose of 17.15 ppm h. To assess the fumigation effectiveness, stomatal conductance and net photosynthesis were monitored. Leaves were analysed for C, N, S, Ca, Mg, K, Fe, Zn, Mn, total soluble sugars, starch, acid-detergent fibre (ADF), lignin and cellulose prior to the incubation in litter bags in mesocosms, and during decomposition along 395 days. Ozone-exposed leaves showed a significant reduction in net photosynthesis and stomatal conductance but did not differ from control leaves in all the chemical parameters analysed. Nevertheless, leaf decomposition rate was lower in treated leaves. The main differences between the models describing the mass loss in exposed and control leaves were played by ADF for exposed leaves and by lignin for control leaves, as well as by N, that showed a greater contribution in the model for the exposed leaves. Ozone fumigation of Q. ilex results in leaf litter decomposition slowing down, mainly due to ADF joint dynamics with the other variables describing mass decay, even if no detectable changes in initial leaf composition occur.
The following values have no corresponding Zotero field: pub-location: 22 RUE DE PALESTRO, PARIS, 75002, FRANCE publisher: SPRINGER FRANCE
Keywords: decomposition; Leaf chemistry; Litter bags and mesocosms

Litter diversity, fungal decomposers and litter decomposition under simulated stream intermittency - Bruder, Andreas; Chauvet, Eric; Gessner, Mark O. (Functional Ecology, 2011)
1. The drying of stream channels resulting from flow interruption is expected to increase as a consequence of climate change. Implications for aquatic organisms and processes are profound. We assessed whether riparian diversity can partially buffer against consequences of drying on fungal decomposers and leaf litter decomposition, an important ecosystem process. 2. Our central hypothesis was that during dry periods recalcitrant leaf litter with high water-holding capacity would extend the window of opportunity for microbial activity in less recalcitrant litter when both litter types are mixed, and that this would lead to a positive litter diversity effect on decomposition. To test for such interactive effects, we conducted a diversity experiment in a Mediterranean stream, in which alder and oak litter, and a mixture of both, was subjected to various drying regimes differing in intensity and timing. 3. Drying regime affected both fungal decomposers and the decomposition rate of alder litter. Effects were observed both immediately and 3 weeks after stream flow resumed. Small differences in the timing of the dry period influenced both decomposition rate and measures of fungal performance (i.e. biomass and sporulation activity). Litter mixing, in contrast, had no effect on either decomposition or fungal decomposers, although mixing increased moisture retention in alder litter as required for the mechanism hypothesized to lead to a diversity effect. 4. Given the contrasting traits of the litter types used in the experiment, our results imply that riparian tree diversity is unlikely to buffer against increased frequencies of stream flow disruption expected in the face of climate change. It appears, however, that the precise timing of dry periods and high-flow events will strongly influence the extent to which stream food webs can exploit the resources supplied by riparian vegetation in the form of leaf litter.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: aquatic hyphomycetes; biodiversity and ecosystem functioning; decomposition; Drought; litter diversity; litter traits; stream intermittency

The fate of condensed tannins during litter consumption by soil animals - Coulis, Mathieu; Hättenschwiler, Stephan; Rapior, Sylvie; Coq, Sylvain (Soil Biology and Biochemistry, 2009)
Condensed tannins (CT) can strongly affect litter decomposition, but their fate during the decomposition process, in particular as inﬂuenced by detritivore consumption, is not well understood. We tested the hypothesis that litter CT are reduced by the gut passage of two functionally distinct detritivores of Mediterranean forests, the millipede Glomeris marginata, and the land snail Pomatias elegans, as a ﬁxed proportion of initial litter CT, but more so in Pomatias since snails are known to have a more efﬁcient enzymatic capacity. Contrary to our hypothesis, both detritivore species reduced litter CT to near zero in their faecal pellets irrespective of the wide range in initial leaf litter CT concentrations of 9–188 mg g 1 d m among three Mediterranean tree species (Pistacia terebinthus, Quercus ilex, Alnus glutinosa) and different decomposition stages of their litter. The almost complete disappearance of CT even from some litter types highly concentrated in CT, due to either degradation by gut microorganism or complexation of CT into insoluble high molecular weight structures, suggests a high ‘‘de-tanning’’ efﬁciency across functionally distinct detritivore species. The transformation of CT-rich litter into virtually CT-free faecal pellets by detritivores might be highly relevant for the subsequent decomposition process in ecosystems with a high macrofauna abundance and CT-rich plant species such as Mediterranean forests.
Keywords: decomposition; Glomeris marginata; Macrofauna; mediterranean forest; polyphenols; Pomatias elegans; Tree leaf litter

The fate of condensed tannins during litter consumption by soil animals - Coulis, Mathieu; Hättenschwiler, Stephan; Rapior, Sylvie; Coq, Sylvain (Soil Biology and Biochemistry, 2009)
Condensed tannins (CT) can strongly affect litter decomposition, but their fate during the decomposition process, in particular as inﬂuenced by detritivore consumption, is not well understood. We tested the hypothesis that litter CT are reduced by the gut passage of two functionally distinct detritivores of Mediterranean forests, the millipede Glomeris marginata, and the land snail Pomatias elegans, as a ﬁxed proportion of initial litter CT, but more so in Pomatias since snails are known to have a more efﬁcient enzymatic capacity. Contrary to our hypothesis, both detritivore species reduced litter CT to near zero in their faecal pellets irrespective of the wide range in initial leaf litter CT concentrations of 9–188 mg g 1 d m among three Mediterranean tree species (Pistacia terebinthus, Quercus ilex, Alnus glutinosa) and different decomposition stages of their litter. The almost complete disappearance of CT even from some litter types highly concentrated in CT, due to either degradation by gut microorganism or complexation of CT into insoluble high molecular weight structures, suggests a high ‘‘de-tanning’’ efﬁciency across functionally distinct detritivore species. The transformation of CT-rich litter into virtually CT-free faecal pellets by detritivores might be highly relevant for the subsequent decomposition process in ecosystems with a high macrofauna abundance and CT-rich plant species such as Mediterranean forests.
Keywords: decomposition; Glomeris marginata; Macrofauna; mediterranean forest; polyphenols; Pomatias elegans; Tree leaf litter

Leaf-Litter Mixtures Affect Breakdown and Macroinvertebrate Colonization Rates in a Stream Ecosystem - Abelho, Manuela (International Review of Hydrobiology, 2009)
Previous work in terrestrial and aquatic ecosystems has suggested that the relationship between breakdown rates of leaf litter and plant species richness may change unpredictability due to non-additive effects mediated by the presence of key-species. By using single- and mixed-species leaf bags (7 possible combinations of three litter species differing in toughness; common alder [Alnus glutinosa ], sweet chestnut [Castanea sativa ], and Spanish oak [Quercus ilex ilex ]), I tested whether leaf species diversity, measured as richness and composition, affects breakdown dynamics and macroinvertebrate colonization (abundance, richness and composition) during 90 days incubation in a stream. Decomposition rates were additive, i.e., observed decomposition rates were not different from expected ones. However, decomposition rates of individual leaf species were affected by the mixture, i.e., there were species-specific responses to mixing litter. The invertebrate communities colonizing the mixtures were not richer and more diverse in mixtures than in single-species leaf bags. On the opposite, mixing leaf species had a negative, non-additive effect on rates of shredder and taxa colonization and on macroinvertebrate diversity. (© 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)
The following values have no corresponding Zotero field: publisher: WILEY-VCH Verlag
Keywords: Biodiversity; decomposition; FOREST; richness; shredders

Leaf-Litter Mixtures Affect Breakdown and Macroinvertebrate Colonization Rates in a Stream Ecosystem - Abelho, Manuela (International Review of Hydrobiology, 2009)
Previous work in terrestrial and aquatic ecosystems has suggested that the relationship between breakdown rates of leaf litter and plant species richness may change unpredictability due to non-additive effects mediated by the presence of key-species. By using single- and mixed-species leaf bags (7 possible combinations of three litter species differing in toughness; common alder [Alnus glutinosa ], sweet chestnut [Castanea sativa ], and Spanish oak [Quercus ilex ilex ]), I tested whether leaf species diversity, measured as richness and composition, affects breakdown dynamics and macroinvertebrate colonization (abundance, richness and composition) during 90 days incubation in a stream. Decomposition rates were additive, i.e., observed decomposition rates were not different from expected ones. However, decomposition rates of individual leaf species were affected by the mixture, i.e., there were species-specific responses to mixing litter. The invertebrate communities colonizing the mixtures were not richer and more diverse in mixtures than in single-species leaf bags. On the opposite, mixing leaf species had a negative, non-additive effect on rates of shredder and taxa colonization and on macroinvertebrate diversity. (© 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)
Keywords: Biodiversity; decomposition; FOREST; richness; shredders

The breakdown of leaves of poplar and holm oak in three Moroccan streams : effect of burial in the sediment - Naamane, B; Chergui, H; Pattee, E (Annales de Limnologie - International Journal of Limnology, 1999)
Weight loss of leaves of Populus nigra and Quercus ilex was observed in coarse-mesh bags exposed in three watercourses and their sediment (-30 and -50 cm) near the city of Fes. The watercourses were: Oued Sebou (a river), Oued Sidi-Harazem (issuing from a warm spring), and Ain Chkef (a cold spring). Weight loss was faster at the surface than within the sediment. Weight loss was faster in poplar than in the tough holm oak leaves. At all levels, weight loss was fastest in Oued Sebou where the water flowed faster both at the surface and within the coarser sediment. It was slowest in the cold spring. Thus the influence of leaf texture, current velocity, and temperature were stressed
Keywords: burial; decomposition; Holm oak; Poplar; watercourse

Decomposition of the organic matter in two forest ecosystems (Natural Park of Montseny, Spain) - I. Abundance, biomass and distribution of the soil microarthropods - Andres, P; Athias-Binche, F (VIE ET MILIEU-LIFE AND ENVIRONMENT, 1998)
This paper represents the first part of a larger work concerning the importance of the oribatid mites in the edaphic trophic chains of two forests (holm-oak and beech woods) under Mediterranean conditions. We offer here the data relating to annual changes of abundance, biomass and vertical distribution of the mesofauna sorted according taxonomic and trophic criteria. The soil was divided into three layers : fresh fallen leaves (L), fermentation layer (F) and organic horizon (S). Rate of leaf imput, dynamics of decomposition, environmental trophic supply, physical structure of the soil and seasonal drought constitute the factors determining the richness and the spatial arrangement of the fauna.
Keywords: decomposition; green oak woodlands; microarthropods; Soil

Decomposition of the organic matter in two forest ecosystems (Natural Park of Montseny, Spain) - I. Abundance, biomass and distribution of the soil microarthropods - Andres, P.; Athias-Binche, F. (VIE ET MILIEU-LIFE AND ENVIRONMENT, 1998)
This paper represents the first part of a larger work concerning the importance of the oribatid mites in the edaphic trophic chains of two forests (holm-oak and beech woods) under Mediterranean conditions. We offer here the data relating to annual changes of abundance, biomass and vertical distribution of the mesofauna sorted according taxonomic and trophic criteria. The soil was divided into three layers : fresh fallen leaves (L), fermentation layer (F) and organic horizon (S). Rate of leaf imput, dynamics of decomposition, environmental trophic supply, physical structure of the soil and seasonal drought constitute the factors determining the richness and the spatial arrangement of the fauna.
The following values have no corresponding Zotero field: pub-location: LABORATOIRE ARAGO, BP 44, 66651 BANYULS-SUR-MER CEDEX, FRANCE publisher: OBSERVATOIRE OCEANOLOGIQUE BANYULS
Keywords: decomposition; green oak woodlands; microarthropods; Soil

Field decomposition of leaf litters: earthworm–microorganism interactions—the ploughing-in effect - Cortez, J.; Bouché, M. B. (Soil Biology and Biochemistry, 1998)
We describe a new decomposition model including the consequences of earthworm mechan- ical activity, especially the ploughing-in eect. In an experiment we tested this ploughing-in eect on the disappearance of leaf litter from four tree species (sessile oak, Quercus petraea L., holm oak, Quer- cus ilex L., sweet chestnut, Castanea sativa Mill and beech, Fagus sylvatica L.) during two 2 y exposure at the site of Anduze which contained the highest earthworm biomass. Our experiment, carried out with leaf litter placed in litterbags allowing (0.5 cm mesh size) or preventing (0.1 cm mesh size) the access of earthworms, con®rms (1) the rates of litter decomposition observed in the ®rst experiment and (2) the important eect of earthworms on litter decomposition (from 20.5% to 30.2% depending on the litter). The breakdown of the dierent litters by soil fauna varied from 24.2% to 40.6% depending on the litters after 2 y exposure in the ®eld at Anduze and the litter decomposition rate was increased by a mean factor of about 5.2. We describe a technique for detecting litter contamination attributed to earthworm casts. This technique is based on the change of the litter total weight loss (TWL)-to-litter total C loss (TCL) ratios which varied from 0.652 to 0.915 in the presence of earthworms and were close to 1 (from 0.952 to 0.995) in the absence of earthworms. We assumed that this large change in these ratios indicated a mineral contamination of litters due to earthworm casting. This hypothesis was con®rmed by the litter ash contents varying from 2.6% to 9.6% with earthworms and from 1.3% to 2.1% without earthworms only. These results point out the ecological importance of contamination of the litter by casts during decomposition.
Keywords: decomposition; earthworm; litter; microbial decomposition; ploughing-in (voyant); weight loss

Field decomposition of leaf litters: earthworm–microorganism interactions—the ploughing-in effect - Cortez, J; Bouché, M B (Soil Biology and Biochemistry, 1998)
We describe a new decomposition model including the consequences of earthworm mechan- ical activity, especially the ploughing-in eect. In an experiment we tested this ploughing-in eect on the disappearance of leaf litter from four tree species (sessile oak, Quercus petraea L., holm oak, Quer- cus ilex L., sweet chestnut, Castanea sativa Mill and beech, Fagus sylvatica L.) during two 2 y exposure at the site of Anduze which contained the highest earthworm biomass. Our experiment, carried out with leaf litter placed in litterbags allowing (0.5 cm mesh size) or preventing (0.1 cm mesh size) the access of earthworms, con®rms (1) the rates of litter decomposition observed in the ®rst experiment and (2) the important eect of earthworms on litter decomposition (from 20.5% to 30.2% depending on the litter). The breakdown of the dierent litters by soil fauna varied from 24.2% to 40.6% depending on the litters after 2 y exposure in the ®eld at Anduze and the litter decomposition rate was increased by a mean factor of about 5.2. We describe a technique for detecting litter contamination attributed to earthworm casts. This technique is based on the change of the litter total weight loss (TWL)-to-litter total C loss (TCL) ratios which varied from 0.652 to 0.915 in the presence of earthworms and were close to 1 (from 0.952 to 0.995) in the absence of earthworms. We assumed that this large change in these ratios indicated a mineral contamination of litters due to earthworm casting. This hypothesis was con®rmed by the litter ash contents varying from 2.6% to 9.6% with earthworms and from 1.3% to 2.1% without earthworms only. These results point out the ecological importance of contamination of the litter by casts during decomposition.
Keywords: decomposition; earthworm; litter; microbial decomposition; ploughing-in (voyant); weight loss

Long-term CO 2-enrichment in a Mediterranean natural forest: An application of large Open Top Chambers - Angelis, P De; Scarascia-Mugnozza, G E (Chemosphere, 1998)
It is crucial to be able to anticipate the possible effects of environmental changes on the Mediterranean woodland communities given their essential role on protecting lands that are under a strong pressure by man and climate. Predictions of the effects of increasing C0~ concentration on plants have been inferred by short- and long-term studies, conducted at different scales and by different technologies. Open Top Chambers (OTCs) are experimental facilities that have been widely used to expose field grown plants to different pollutant gases, and more recently to elevated [CO2] . In this paper, we present the natural site and the experimental system (six large OTCs enclosing clumps of natural vegetation) that we have been utilizing for 3 years, to assess the impact of elevated [CO2] on a Mediterranean natural forest community. The results show that large OTCs can be usefully used to simulate C02 doubling even under the harsh environmental conditions of the mediteffanean region
Keywords: decomposition; Elevated CO3; leaf litter; Mediterranean forest (voyant)

Long-term CO 2-enrichment in a Mediterranean natural forest: An application of large Open Top Chambers - Angelis, P. De; Scarascia-Mugnozza, G. E. (Chemosphere, 1998)
It is crucial to be able to anticipate the possible effects of environmental changes on the Mediterranean woodland communities given their essential role on protecting lands that are under a strong pressure by man and climate. Predictions of the effects of increasing C0~ concentration on plants have been inferred by short- and long-term studies, conducted at different scales and by different technologies. Open Top Chambers (OTCs) are experimental facilities that have been widely used to expose field grown plants to different pollutant gases, and more recently to elevated [CO2] . In this paper, we present the natural site and the experimental system (six large OTCs enclosing clumps of natural vegetation) that we have been utilizing for 3 years, to assess the impact of elevated [CO2] on a Mediterranean natural forest community. The results show that large OTCs can be usefully used to simulate C02 doubling even under the harsh environmental conditions of the mediteffanean region
Keywords: decomposition; Elevated CO3; leaf litter; Mediterranean forest (voyant)

The aquatic processing of sclerophyllous and malacophyllous leaves on a Mediterranean island (Corsica) : spatial and temporal pattern - Schwarz, A E; Schwoerbel, J (Annales de Limnologie - International Journal of Limnology, 1997)
Leaves of two species, alder (Alnus glutinosa) and holm-oak (Quercus ilex), were exposed in bags of two mesh sizes in two climatically contrasting sites of a Corsican softwater stream. Leaves were incubated both in winter and in summer for about 6 months. The field experiment was designed to determine the influence of both spatial (climate) and temporal (season) variations of temperature, as well as differences in the chemical and physical properties of sclerophyilous and malacophyllous leaves, on leaf decomposition rates. Comparisons were made between leaves colonized by macroinvertebrates and leaves protected by finemesh. In winter and summer, holm-oak leaves were colonized much less by macroinvertebrates than alder leaves. Spatial and temporal differences in leaf litter processing were mainly dependent on three factors (i) the chemical and physical properties of the leaves, (ii) the abundance of macroinvertebrates in the sediment and (iii) the temperature. The climatical pattern of temperature had a greater influence than its seasonal pattern. In contrast with many other studies, abiotic factors dominated over biotic factors in this study.
Keywords: alnus glutinosa; decomposition; leaves; macroinvertebrates; Mediterranean ecosystem; Quercus ilex; Temperature

Decomposition of mediterranean leaf litters: A microcosm experiment investigating relationships between decomposition rates and litter quality - Cortez, J; Demard, J M; Bottner, P; Jocteur Monrozier, L (Soil Biology and Biochemistry, 1996)
he decomposition of four mediterranean species leaf litter (Sessile oak, Quercus petraea L.; Holm oak, Quercus ibex L.; Sweet chestnut, Castanea satiua Mill and beech, Fagus syluatica L.) was studied for 90 days under controlled conditions. Respiration and litter mass loss were measured in three types of microcosms: (1) Soil only; (2) Soil + l-y old litter and (3) Soil + l-y old litter + newly senescent litter (freshly fallen). Variations in chemical composition of the litters were determined before and after incubation by the pyroanalysis method. For newly senescent litters decomposition rates per day Kco, (calculated from CO, release) and K, (calculated from mass losses) fitted to the first order exponential decay decreased as follows: sessile oak (Kc,_,, = 0.0043; K, = 0.0049) > holm oak (Km, = 0.0031; K, = 0.0040) = beech (&o~ = 0.0030; K, = 0.0030) > sweet chestnut (Kc% = 0.0001; K,, = non- significant regression); For l-y old litters sweet chestnut (Ko,, = O.oo40, K, = 0.0065) > sessile oak (KEO, = 0.0035; K, = 0.0039) > beech (Kcc,, = 0.0030; K, = non-significant regression). All litters showed a reduction of lipid (mean loss 90.5%), hydrosoluble (mean loss, 54.2%), hemicellulose plus cellulose (mean loss, 40.6%) content and a relative increase of lignin content (mean gain, 34.4%). Among indicators of litter quality (C-to-N ratio, %N, %lignin, lignin-to-N ratio, HLQ), only some of them were correlated with litter decay. The best relationships were established between the decomposition rates (K,) and parameters integrating lignin contents (I = 0.997; n = 3; P < 0.01). The decomposition of l-y old litters fitted well with most of these parameters (0.999 < I < 0.997; n = 3; P < 0.01) in contrast to newly senescent litters
Keywords: Cellulose; decomposition; hemicellulose; leaf litter; Lignin; litter quality (voyant); mass loss; mineralization

Local variations of ecosystem functions in Mediterranean evergreen oak woodland - Joffre, R; Rambal, S; Romane, F (Ann. For. Sci., 1996)
The spatial variation of ecosystem function was studied in a Quercus ilex coppice growing on hard limestone with low soil water availability. Spatial structures obtained from data on i) leaf area index, ii) leaf litterfall, and iii) leaf litter decay rate were compared. All these variables were sampled on 26 points located within a 30 x 30 m plot. Mean average leaf litterfall over 10 years (1984-1993) was 254 g.m-2. For each year, the semivariograms of leaf litterfall have been fitted using a spherical model. The values of the range parameter (indicating the limit of the spatial dependence) ranged from 6.4 to 10.3 m, very close to the value (9.2 m) of the range parameter obtained when fitting the semivariogram of mean leaf litterfall over 10 years. This result indicates the temporal persistence of the spatial pattern of leaf litterfall. The leaf area index (LAI) was estimated at the same points with a plant canopy analyzer. The mean value was 2.96 ± 0.30. The limit of spatial dependence for LAI was very close to that obtained for leaf litterfall (range = 8.5 m). The litter decomposition pattern was obtained through analysis of litter samples taken at the same points. The percentage of ash-free litter mass remaining (LMR) estimated using near-infrared reflectance spectroscopy indicates the stage of decomposition. It decreased strongly between the surface (mean value 85.6%) and the subsurface layers (mean value 63.4%). The two semivariograms can be described by spherical models, the sill being reached at a range of 21.4 and 18.7 m for the surface and subsurface layers, respectively. The two variables directly related to the structure of the canopy (LAI and leaf litterfall) exhibited close spatial dependence and differed from the soil process-related variables (stage of decomposition) whose ranges were approximately double. These geostatistical analyses show promise for use in developing hypotheses concerning the spatial scale of process-pattern interactions.
Keywords: decomposition; geostatistics; leaf area index; litterfall; local variation; Quercus ilex

QUERCUS-ILEX L LITTER DECOMPOSITION AND MINERAL EVOLUTION IN AN EVERGREEN OAK WOODLAND IN MAJORCA (BALEARIC-ISLANDS, SPAIN) - XAMENA, J; García, C; MOREY, M (RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES, 1992)
The aim of this contribution is to describe the decomposition processes of litter in an evergreen oak wood and the evolution of the four cations; calcium, magnesium, sodium and potassium.
Keywords: decomposition; litter; minerals